2011
DOI: 10.5511/plantbiotechnology.11.0119a
|View full text |Cite
|
Sign up to set email alerts
|

Induction of double flowers in Pharbitis nil using a class-C MADS-box transcription factor with Chimeric REpressor gene-Silencing Technology

Abstract: The Chimeric REpressor gene-Silencing Technology (CRES-T) system is a novel reverse genetic method using a chimeric transcriptional repressor fusing an EAR transcriptional repression domain called SRDX. We sought to change the flower shape of Pharbitis nil, a model ornamental flower, using an Arabidopsis transcription factor fused with SRDX. For the first trial modulating flower shape we transformed with the class-C MADS-box transcription factor AGAMOUS (AG) fused with SRDX (AGSRDX). Defects in class-C genes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…We observed phenotypic variation among transgenic lines, but severe phenotypes were not always correlated with higher expression levels of the transgenes (data not shown). It has been reported that when using the CRES-T system, differences in expression level of SRDX fused cDNA do not reflect the severity of the phenotype Sage-Ono et al 2011), and we noticed a similar effect in TCP3SRDX and TCP5SRDX transformants.…”
Section: Generation Of Transgenic I Nil Expressing Tcp3srdx and Tcp5supporting
confidence: 71%
“…We observed phenotypic variation among transgenic lines, but severe phenotypes were not always correlated with higher expression levels of the transgenes (data not shown). It has been reported that when using the CRES-T system, differences in expression level of SRDX fused cDNA do not reflect the severity of the phenotype Sage-Ono et al 2011), and we noticed a similar effect in TCP3SRDX and TCP5SRDX transformants.…”
Section: Generation Of Transgenic I Nil Expressing Tcp3srdx and Tcp5supporting
confidence: 71%
“…These monocot species can be used for studies to modify floral organ development by overexpression or reduction of B-and C-class floral organ identity genes. The chimeric repressor of SRDX has been used successfully to reduce C-class gene expression and produce double-flowered mutants in morning glory and cyclamen (Sage-Ono et al, 2011;Tanaka et al, 2013). Recently, virus-induced gene silencing (VIGS) has been employed to reduce B-or C-class gene expression in ornamental plants such as Aquilegia, Phalaenopsis, and Petunia Hsieh et al, 2013;Kramer et al, 2007;Noor et al, 2014).…”
Section: Future Prospectsmentioning
confidence: 99%
“…In a previous study, Tanaka et al (2013) produced petaloid-stamen-type double-flowered cyclamen by AGAMOUS chimeric repressor expression (CRES-T). Similarly, petaloidstamen-type double flowers in other ornamental flowers were also produced by AG-like gene silencing (Narumi et al, 2008;Sage-Ono et al, 2011). Therefore, it is suspected that the petaloidy of stamens even in other naturally occurring double-flowered cyclamens might be caused by the reduced expression of AG-like genes in whorl 3.…”
Section: Discussionmentioning
confidence: 99%